CANDI PERWARA PADA PERCANDIAN IJO, PLAOSAN LOR, DAN PLAOSAN KIDUL: SEBUAH KAJIAN ARSITEKTUR DAN TINJAUAN INSKRIPSI - Widyahastuti, Dwi Ratna Sylvia; Munandar, Agus Aris (UI Scholars Hub, 2026)
Temple or Candi are sacred Hindu and Buddhist buildings constructed in accordance with the prescriptions of the Vāstuśāstra, including subsidiary temple or candi perwara. This study examines the candi perwara of the Ijo, Plaosan Lor, and Plaosan Kidul Temple Complex to analyze their technical aspects, religious functions, and chronological positions within their respective temple complexes. Employing a descriptive-comparative method and a historical-archaeological approach supported by epigraphical review, the research identifies similarities in the roof forms and ornamental reliefs. Differences are observed in ground plans, stone materials, construction systems, vestibule, base forms, body variations, cella, and decorative motifs. The findings suggest that the architecture of these candi perwara represents variations in architectural form and function of candi perwara between the 8th—10th Century. This diversity reflects the intellectual concepts of their builders and the religious life of the Mataram Kuno Kingdom during that period.